Cellular senescence and aging: the role of B‐MYB. Issue 5 (1st July 2014) - Mowla, Sophia N.; Lam, Eric W.‐F.; Jat, Parmjit S.
Summary Cellular senescence is a stable cell cycle arrest, caused by insults, such as: telomere erosion, oncogene activation, irradiation, DNA damage, oxidative stress, and viral infection. Extrinsic stimuli such as cell culture stress can also trigger this growth arrest. Senescence is thought to have evolved as an example of antagonistic pleiotropy, as it acts as a tumor suppressor mechanism during the reproductive age, but can promote organismal aging by disrupting tissue renewal, repair, and regeneration later in life. The mechanisms underlying the senescence growth arrest are broadly considered to involve p16INK4A‐pRB and p53‐p21CIP1/WAF1/SDI1 tumor suppressor pathways; but it is not known what makes the senescence arrest stable and what the critical downstream targets are, as they are likely to be key to the establishment and maintenance of the senescent state. MYB‐related protein B (B‐MYB/MYBL2), a member of the myeloblastosis family of transcription factors, has recently emerged as a potential candidate for regulating entry into senescence. Here, we review the evidence which indicates that loss of B‐MYB expression has an important role in causing senescence growth arrest. We discuss how B‐MYB acts, as the gatekeeper, to coordinate transit through the cell cycle, in conjunction with the multivulval class B (MuvB) complex and FOXM1 transcription factors. We also evaluate the evidence connecting B‐MYB to the mTOR nutrient signaling pathway and suggest that inhibition of this pathway leading to an extension of healthspan may involve activation of B‐MYB.